2014
DOI: 10.1167/iovs.14-15382
|View full text |Cite
|
Sign up to set email alerts
|

A Homozygous Missense Mutation in NEUROD1 Is Associated With Nonsyndromic Autosomal Recessive Retinitis Pigmentosa

Abstract: Citation: Wang F, Li H, Xu M, et al. A homozygous missense mutation in NEUROD1 is associated with nonsyndromic autosomal recessive retinitis pigmentosa. Invest Ophthalmol Vis Sci. 2015;56:150-155. DOI: 10.1167/iovs.14-15382 PURPOSE. Mutations in the same gene can lead to different clinical phenotypes. In this study, we aim to identify novel genotype-phenotype correlations and novel disease genes by analyzing an unsolved autosomal recessive retinitis pigmentosa (ARRP) Han Chinese family.METHODS. Whole exome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…IRDs demonstrate both extensive clinical and genetic heterogeneity. To date, nearly 300 genes have been identified that associate with various forms of IRDs ( https://sph.uth.edu/retnet/ ) (accessed Jun 23 rd , 2017) and they are involved in a wide range of biological pathways such as photo-transduction 1 , 2 , ciliogenesis 3 , 4 , pre-mRNA splicing 5 , 6 , transcription regulation 7 and protein transport/quality control 8 , 9 . Nevertheless, novel disease-causing genes and pathways are still being identified by whole exome sequencing or whole genome sequencing, adding to the pathological mechanisms of retinal dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…IRDs demonstrate both extensive clinical and genetic heterogeneity. To date, nearly 300 genes have been identified that associate with various forms of IRDs ( https://sph.uth.edu/retnet/ ) (accessed Jun 23 rd , 2017) and they are involved in a wide range of biological pathways such as photo-transduction 1 , 2 , ciliogenesis 3 , 4 , pre-mRNA splicing 5 , 6 , transcription regulation 7 and protein transport/quality control 8 , 9 . Nevertheless, novel disease-causing genes and pathways are still being identified by whole exome sequencing or whole genome sequencing, adding to the pathological mechanisms of retinal dystrophy.…”
Section: Introductionmentioning
confidence: 99%
“…This variant was identified by whole‐exome sequencing and was predicted to affect a highly conserved amino acid. Different in silico analysis algorithms yielded prediction scores ranging from “damaging” to “benign.” Segregation analysis was consistent with the variant being causative, supporting the essential role of NEUROD1 in maintaining adult photoreceptors in humans . It is interesting that these cases had isolated retinitis pigmentosa with no neurological features or disorders in glucose metabolism.…”
Section: Discussionmentioning
confidence: 65%
“…Recently, a NEUROD1 homozygous missense mutation, p.Val242Ile, has been identified in a consanguineous family with autosomal recessive non‐syndromic retinitis pigmentosa . This variant was identified by whole‐exome sequencing and was predicted to affect a highly conserved amino acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the HRD field, the molecular diagnosis of disease cases also benefits a lot from a variety of NGS-based methods, including whole exome sequencing and targeted capture sequencing. Correspondingly, the molecular diagnosis rate of HRD cases has been significantly improved [4][5][6][7][8][9][10][11][12][13] , and a series of novel HRD-associated genes have been identified [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] .…”
Section: Introductionmentioning
confidence: 99%